Pharmacokinetics and adverse effects of voriconazole administered orally q72 hours in healthy cats - Bowyer, Ashley N. (My University, 2025)
Objective: Some cats with systemic fungal disease fail to respond to itraconazole and fluconazole, thus this study aimed to investigate pharmacokinetics and adverse effects of voriconazole in cats with an extended dosing protocol. Methods: Nine healthy cats were administered voriconazole at a loading dose of 25 mg/cat PO followed by 12.5 mg/cat PO every 72 hours for 16 days. Plasma voriconazole concentration was measured: 4, 8, and 12 hours after voriconazole administration on days 0 and 15; on days 3, 6, 9, 12, and 15 before drug administration; and every 48 hours for 6 days after the last dose. Pre- and post-treatment physical examination, electroretinography (ERG), electrocardiography (ECG), complete blood count, serum chemistry, and urinalysis were performed. Results: Plasma trough concentration 72 hours after the first dose was 1.80 ± 0.48 μg/mL, increasing to 4.53 ±1.05 μg/mL immediately prior to the last dose (P < .001). Half-life also significantly increased from day 0 (5.5 ± 1.4 days) to day 15 (11.9 ± 5.2 days) (P = .001). Adverse effects included weight loss (mean = 0.24 kg in 8/9 cats), vomiting (4/9), and sporadic miosis (3/9). The mean ERG b-wave amplitude decreased from 317 to 213 μV with treatment (P < .001). No clinical vision deficits were appreciated. Conclusions: Voriconazole had a long half-life and continued accumulation in cats when administered orally at 72-hour intervals. Further research is needed to determine the optimum dosage and whether decreased ERG b-wave amplitude is a clinically significant effect.
Keywords: Voriconazole; Oral administration; Pharmacokinetics; Cats; Adverse effects